Prognostic implications of PD-L1 expression in patients with soft tissue sarcoma. Issue 1 (December 2016) - Kim, Chan; Kim, Eun; Jung, Hun; Chon, Hong; Han, Jung; Shin, Kyoo-Ho; Hu, Hyuk; Kim, Kyung; Choi, Young; Kim, Sunghoon; Lee, Young; Suh, Jin-Suck; et al.
Abstract Background The PD-1/PD-L1 axis plays a paramount role in the immune escape of tumor cells by negative regulation of T-cell functions. The aim of the present study was to characterize the PD-L1 expression pattern and its clinical implication in soft-tissue sarcomas (STS). Methods We analyzed PD-L1 expression in 82 STS patients with 5 subtypes: rhabdomyosarcoma, synovial sarcoma, Ewing sarcoma, epithelioid sarcoma, and mesenchymal chondrosarcoma. Results The median age at diagnosis was 26 (range: 1–78) and the male to female ratio was 1.6. The majority (80 %) of patients showed locoregional disease rather than metastatic disease at diagnosis. Thirty-five cases (43 %) showed PD-L1 expression and the proportion of PD-L1 expression was significantly different according to histologic subtypes (P  = 0.004); highest in epithelioid sarcoma (100 %, 7/7), followed by synovial sarcoma (53 %, 10/19), rhabdomyosarcoma (38 %, 12/32), and Ewing sarcoma (33 %, 6/18), while it was not expressed in mesenchymal chondrosarcoma (0 %, 0/6). STS patients with PD-L1 expression had worse overall survival compared with those without PD-L1 expression (5-year survival rate: 48 %vs . 68 %, P  = 0.015). The Cox proportional hazard model adjusted for histologic subtype, initial metastasis, and PD-L1 expression showed that PD-L1 expression was significantly associated with shorter overall survival (P  = 0.037, HR 2.57, 95 % CI 1.060–6.231). Conclusion We have confirmed PD-L1 expression in various STS of young population and demonstrated its independent negative prognostic role, thereby suggesting the PD-1/PD-L1 axis as a potential therapeutic target for the treatment of young STS patients.